Respuesta :
B
n
=
2
Explanation:
The first thing that you need to do here is to use the frequency of the emitted photon to calculate its wavelength.
As you know, frequency and wavelength have an inverse relationship described by the equation
ν
⋅
λ
=
c
−−−−−−−−
Here
ν
is the frequency of the photon
c
is the speed of light in a vacuum, usually given as
3
⋅
10
8
m s
−
1
Plug in your value to find
λ
=
3
⋅
10
8
.
m
s
−
1
6.90
⋅
10
14
s
−
1
=
4.348
⋅
10
−
7
n
=
2
Explanation:
The first thing that you need to do here is to use the frequency of the emitted photon to calculate its wavelength.
As you know, frequency and wavelength have an inverse relationship described by the equation
ν
⋅
λ
=
c
−−−−−−−−
Here
ν
is the frequency of the photon
c
is the speed of light in a vacuum, usually given as
3
⋅
10
8
m s
−
1
Plug in your value to find
λ
=
3
⋅
10
8
.
m
s
−
1
6.90
⋅
10
14
s
−
1
=
4.348
⋅
10
−
7